Caracterização molecular de espécies fúngicas isoladas de processos infecciosos de pacientes da Fundação de Hematologia e Hemoterapia do Amazonas - Silva, Lucyane Mendes da (2019)
The incidence of fungal infections has increased worldwide, especially in the hospital setting, representing one of the major infectious complications in hospitalized patients and contributing to high morbidity and mortality. Particularly in patients with hematological diseases, who undergoing intensive chemotherapy therapy, or who deplete their immune system, leaving them susceptible to developing infections such as opportunistic drugs, neutropenia and other risk factors. The most common etiological agents responsible for infectious processes are Aspergillus spp. 38-80% and Candida spp. 28-58%, being related to resistance to antifungals widely used in therapy. Research at the genetic level contributes to a better understanding of the molecular epidemiology and evolutionary mechanisms of these pathogens. Thus, this study aimed to characterize the molecular level of fungal species that cause infectious processes of patients treated by the Amazon Hospital Hematology and Hemotherapy Foundation. This is a cross-sectional, prospective and descriptive study. The data collection period was from November 2017 to October 2018. The records were used through medical records, SoftLab system and iDoctor. Identification of yeast species and susceptibility testing (Fluconazole, Voriconazole, Caspofungin, Micafungin, Amphotericin B and Flucytosine) were performed with the automated Vitek-2 Compact equipment. The identification of filamentous fungal species was performed with the Internal Transcript Spacer gene. Also within the scope of molecular epidemiology, genotyping by the Multi Locus Sequence Typing method was performed to define the sequence types and common ancestors of the clinical species and phylogenetic tree. With the initial analysis of the results obtained, we found a total of 162 patients, 91 (56.2%) males and 71 (44%) females, with a mean age of 32 years; all of them of Brazilian nationality, being 150 (92.6%) born in the state of Amazonas; 66 (41%) did not study; 110 (68%) do not have occupation. Of the patients diagnosed with a haematological disease, acute lymphoblastic leukemia was the most frequent with 64 (39%) cases, followed by Acute Myeloid Leukemia with 39 (24%). A total of 34 (21%) patients died. Of the 285 samples collected for microbiological examinations, 241 (84.5%) blood culture, 39 (13.75%) urine, 2 (0.70%) skin, 1 (0.35%) bone marrow, 1 (0, 35%) sputum, 1 (0.35%) catheter secretion. Of these, 33 (12.0%) have fungi growth, while 91 (32.0%) bacteria. There was no microbial growth in 161 (56.0%). Of the 162 patients with suspected infectious process, 30 (18.51%) were infected by fungal species where 13 (39.39%) Penicillium spp., 12 (36.36%) blood samples were isolated. Most yeast individuals identified within the sensitive range ahead of tested antifungals did not detect any resistance genes. Only two individuals with Candida glabrata have reduced sensitivity to Fluconazole. With these results, it was possible to identify and contextualize several important aspects of these pathogens, such as issues related to public health, clinical, molecular epidemiology and recommended therapy for the most diverse infectious processes caused by these agents